1994
DOI: 10.1029/94gl00631
|View full text |Cite
|
Sign up to set email alerts
|

The African Superswell

Abstract: Maps of residual bathymetry in the ocean basins around the African continent reveal a broad bathymetric swell in the southeastern Atlantic Ocean with an amplitude of about 500m. We propose that this region of anomalously shallow bathymetry, together with the contiguous eastern and southern African plateaus, form a superswell which we refer to as the African superswell. The origin of the African superswell is uncertain. However, rifting and volcanism in eastern Africa, as well as heat flow measurements in south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
212
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 305 publications
(225 citation statements)
references
References 21 publications
13
212
0
Order By: Relevance
“…Using the system of Clifford (1986) (Schlüter, 2006). Another significant influence for the continent is the African Superswell (Nyblade and Robinson, 1994). This large feature has elevated significant portions of the African continent along a swath running from south of Africa to the middle of the Arabian Peninsula, and has been observed seismically down to the core-mantle boundary (Ritsema et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the system of Clifford (1986) (Schlüter, 2006). Another significant influence for the continent is the African Superswell (Nyblade and Robinson, 1994). This large feature has elevated significant portions of the African continent along a swath running from south of Africa to the middle of the Arabian Peninsula, and has been observed seismically down to the core-mantle boundary (Ritsema et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These three rift zones form a triple junction in the Afar. This area also sits at the northern edge of the African Superswell, a buoyant region under eastern and southern Africa responsible for high residual topography (Nyblade and Robinson, 1994). Rifting in the south continues along the Moving further to the south, the Katanga Belt runs east-west between the Congo and Kalahari Cratons.…”
Section: Introductionmentioning
confidence: 99%
“…It sits between two other regions of anomalous topography and bathymetry, the East African Plateau to the north, and the southeastern Atlantic Ocean basin to the southwest, and together, these regions form the African Superswell [Nyblade and Robinson, 1994] ( Figure 1). By removing the mean global continental elevation from the observed elevations in Africa, and by removing the age-predicted bathymetry from the observed bathymetry in the ocean basins around Africa, Nyblade and Robinson [1994] showed that the long wavelength (i.e., > a few hundred km) anomalous topography and bathymetry associated with the African Superswell is about 500 m. Many shorter wavelength topographic and bathymetric features are superimposed on this long wavelength swell.…”
Section: Introductionmentioning
confidence: 99%
“…Pysklywec and Mitrovica [1999] suggested that dynamic rebound after slab detachment following the cessation of subduction below the Cape Fold Belt at the end of the Triassic may have contributed to present-day elevations over much of southern Africa. And van der Beek et al [2002], citing work by Lowry et al [2000] for the western United States, offered as a possible uplift mechanism the underplating of lowdensity melts, chemically depleted of their basaltic constituents, to the underside of the lithosphere at Nyblade and Robinson, 1994]. Continental shelves and areas where the bathymetry was not corrected for sediment thickness are shown in white.…”
Section: Introductionmentioning
confidence: 99%
“…The mean elevation of these areas is -1 km, -500 m higher than the global average of similar continental areas. Nyblade and Robinson [ 1994] used the term "African superswell" to refer to these areas together with a contiguous, bathymetrically elevated region in the southeastern Atlantic Ocean. The origin of the African superswell is not well understood.…”
Section: Introductionmentioning
confidence: 99%